A comparative study of the back-stepping control and PI control of the three-phase inverter from stability point of view - He, Jinsong (2018)
This project aims to fulfill the stability requirement of the system involved with three-phase inverter, where PI control theory and backstepping control strategy are implemented respectively based on the Nyquist criteria. Three-phase variables will be transformed into dq0 frames before being processed by PI controller and backstepping controller. The direct as well as the quadrature value of the sampled current signals are compared with the reference signal and then processed respectively, meanwhile the calculated dq0 function is converted to three-phase coordinate to provide three-phase duty cycles for the SPMW block to generate the PWM triggering signals for the three-phase inverter [1]. As the standard of power quality needed to be ensured in industrial systems gets higher, modern control strategies have to be adopted in the three-phase inverter, when faced with voltage fluctuations, parameter perturbations, and load disturbance. Specifically, this project focuses on backstepping control strategy which can guarantee the stability of the three-phase inverter based on the Lyapunov criteria. A novel adaptive backstepping approach for the three-phase inverter based on dSPACE DS1103 control board was studied in this report. In addition, a rectified structure of the backstepping nonlinear controller was designed and then validated by simulation in SIMULINK and experiments by applying dSPACE DS1103 [2]. Subsequently, the open-loop and closed-loop hardware experimental results were presented and compared respectively applied with PI control and back-stepping control strategy, based on a real 500 W three-phase inverter with 10 kHz switching frequency. According to simulation results and hardware verification, comparisons between two controllers have been summarized in a table, including significant parameters, number of state variables, static stability, and transit tracking performance. In the end, the final conclusion would be drawn and future work would also be figured out.